Dimensions of Change Management Object in Muhammadiyah Pesantren - Perawironegoro, Djamaluddin; Widodo, Hendro; Sukirman, Sukirman; Wantini, Wantini (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to analyze and find the dimensions of change management objects in Muhammadiyah Pesantren. This study uses a qualitative research approach with a case study research type. The research was conducted at the Muhammadiyah Boarding School Klaten with the director, principal, and teachers as research informants. The qualitative data in this study are interview data, observation data, and document data. Data was collected by researchers from research informants, research locations, and official documents of Islamic boarding schools. Data analysis techniques are carried out through data collection, data codification, data analysis, and conclusion-making. The study’s findings show that the dimensions of the change management object consist of organizational structure, curriculum, learning, and parenting. The process of managing changes in Muhammadiyah Pesantren is carried out by change planning, organizational strengthening, communication and motivation, and evaluation. Change management is carried out continuously in its stages. By making changes to the dimensions that have been mentioned, there is an increase in the productivity of directors, teachers, and students. In addition, there is an increase in pesantren performance in terms of financial income, the number of new students, learning outcomes, several achievements, and cooperation among pesantren residents.